Penguatan Kompetensi Mahasiswa dalam Pengambilan Sampel Air melalui Pendekatan Learning by Doing - Vivi Dia Afrianti Sangkota; Suleman Duengo; Erga Kurniawati; Thayban Thayban (Damhil: Jurnal Pengabdian kepada Masyarakat, 2026)
Water sampling skills are essential competencies for chemistry students because the accuracy of sampling procedures determines the representativeness and reliability of water quality analysis data. However, students still have limited understanding of sampling-point selection, the use of sampling equipment and containers, labeling, preservation, and field measurement of water quality parameters. This community service activity aimed to strengthen students’ competence in water sampling through a learning-by-doing approach. The program employed educational and training methods, including theoretical instruction, equipment demonstrations, field practice, discussion, and evaluation using pretest and posttest instruments. The evaluation covered four indicators: basic principles of water quality and monitoring, sampling-point selection and procedures, equipment use, labeling and sample preservation, and measurement of pH, temperature, turbidity, and dissolved oxygen. The evaluation results showed that the students’ average understanding increased from 58.75% before the training to 84.00% after the training, representing an increase of 25.25%. The highest improvement was found in equipment use, labeling, and sample preservation, with an increase of 27%. Descriptively, these findings indicate that the learning-by-doing approach strengthened students’ understanding and practical skills in water sampling and handling. Similar training should be continued through periodic practice and the development of a student-based water quality monitoring group.